(untitled) (Bangladesh Journal of Infectious Diseases, 2025)
Background: Urinary albumin excretion is recognized as an early marker of renal dysfunction and has been associated with adverse renal outcomes following percutaneous coronary intervention in patients with acute coronary syndrome. Objective: The purpose of this present study was to assess the development of contrast-induced nephropathy among patients with acute coronary syndrome undergoing percutaneous coronary intervention. Methodology: This cross-sectional analytical study was conducted in the Department of Cardiology at the National Heart Foundation Hospital and Research Institute (NHFH & RI), Dhaka, from August 2021 to July 2023. A total of 164 consecutive acute coronary syndrome patients undergoing percutaneous coronary intervention were enrolled and categorized into two groups based on urinary albumin excretion: microalbuminuria and normoalbuminuria. Microalbuminuria (MA) was defined as a urinary albumin-to-creatinine ratio (uACR) of 30–300 mg/g in a random spot urine sample. The relationship between pre-procedural microalbuminuria and the occurrence of contrast-induced nephropathy was further assessed using receiver operating characteristic (ROC) curve analysis. Results: Among the 164 patients, 67 (41%) had microalbuminuria and 97 (59%) had normoalbuminuria. The mean uACR was significantly higher in the microalbuminuria group (73.75 ± 5.6 mg/g) compared to the normoalbuminuria group (16.24 ± 6.43 mg/g). contrast-induced nephropathy developed in 24 patients (36%) in the microalbuminuria group, whereas only 15 patients (16%) in the normoalbuminuria group experienced contrast-induced nephropathy. ROC curve analysis identified a uACR threshold of 223.17 mg/g as the optimal cut-off for predicting contrast-induced nephropathy, with the best balance of sensitivity and specificity. Conclusion: In conclusion, pre-procedural microalbuminuria is significantly associated with an increased risk of contrast-induced nephropathy in acute coronary syndrome patients undergoing percutaneous coronary intervention. Bangladesh Journal of Infectious Diseases, June 2025;12(1):134-140